Transformasi Kompetensi Pendidik melalui Pengendalian Mutu Terintegrasi: Pelajaran dari Program PHBK Akbar di Bojonegoro, Indonesia: Transforming Educator Competence through Integrated Quality Control: Lessons from the PHBK Akbar Program in Bojonegoro, Indonesia. - Aziz, Muhammad; Mazidah, Nur; Ghazali, Mohd Fahmi (OBHE: Jurnal Pascasarjana IAIN Papua, 2026)
Quality assurance in early childhood education (PAUD) is often trapped in administrative formalism that prioritizes bureaucratic compliance over substantive pedagogical transformation. In Indonesia, the challenge of teacher professionalization is often hampered by instructive and top-down quality control mechanisms. This study aims to analyze the integrated quality control (IQC) management strategy in the Akbar PHBK Program in Bojonegoro and its impact on improving educator competency through the lens of Total Quality Management (TQM) and the Plan-Do-Check-Act (PDCA) cycle. Using a qualitative approach with an exploratory case study design, data were collected through in-depth interviews with program managers, trainers, and 12 PAUD educators, supported by participant observation and analysis of quality audit documents. Data were analyzed using Braun and Clarke's thematic analysis technique to identify patterns of quality management integration. The results revealed three crucial findings: First, QC management in the Akbar PHBK successfully internalized a quality culture as a collective moral responsibility, in line with the principles of TQM that are oriented towards character values. Second, the rigid operationalization of the PDCA cycle, particularly in the formative monitoring (Check) and follow-up (Act) stages, has proven effective in facilitating a paradigm shift in teachers from mere administrative compliance to reflective, substantive professionalism. Third, this study identifies a professionalism paradox where the success of local strategies often clashes with fragmented national policy constraints. The novelty of this research lies in the conceptualization of the Integrated Quality Control (IQC) model, which bridges industrial management quality standards with the pedagogical sensitivity of character education. The implications of this study emphasize the need for reform of early childhood education (ECE) quality assurance policies in Indonesia, moving from a traditional inspection model to a clinical supervision system that empowers teachers' agency and democratic autonomy. Lessons from Bojonegoro provide a strategic model for the sustainable development of educator competencies in developing countries